Tratamiento Contable de los Ingresos y Gastos de la Cooperativa COOPROTERXI - Aviles Triviño, Diana Narcisa (2018)
The present case study is oriented to know the accounting treatment of the income and expenses of Cooperativa Cooprotexri, which is dedicated to the preparation of articles with textile material. The accounting records and the Financial Statements, within which are the records of income and expenses, are of utmost importance for companies, partners, control institutions and other stakeholders, through these you can observe and analyze the economic situation of the organizations and financial decisions can be made, management, control, among others. Considering the above, in the present work we start from an antecedent of the Cooperativa Cooproterxi, in which the general information of the same is exposed, the economic activity, its form of organization, among others. Later an analysis of the accounts of the cooperative and its registration form, in which the methods of descriptive research and observation, as an investigation technique the interview was used and as a tool of investigation, the questionnaire. Finally, the result of the study is presented, evaluating the premise about the proper recording of income and expenses by the cooperative.